Dynamic Volumetric Computed Tomography Angiography is an Effective Method to Evaluate Tracheomalacia in Children. (12th April 2022) - Koenigs, Maria; Young, Cody; Lillis, Anna; Morrison, Jessica; Kelly, Natalie; Elmaraghy, Charles; Krishnamurthy, Rajesh; Chiang, Tendy
Abstract : Objective: Standard methods to evaluate tracheal pathology in children, including bronchoscopy, may require general anesthesia. Conventional dynamic proximal airway imaging in noncooperative children requires endotracheal intubation and/or medically induced apnea, which may affect airway mechanics and diagnostic performance. We describe a technique for unsedated dynamic volumetric computed tomography angiography (DV‐CTA) of the proximal airway and surrounding vasculature in children and evaluate its performance compared to the reference‐standard of rigid bronchoscopy. Methods: Children who had undergone DV‐CTA and bronchoscopy in one‐year were retrospectively identified. Imaging studies were reviewed by an expert reader blinded to the bronchoscopy findings of primary or secondary tracheomalacia. Airway narrowing, if present, was characterized as static and/or dynamic, with tracheomalacia defined as >50% collapse of the tracheal cross‐sectional area in exhalation. Pearson correlation was used for comparison. Results: Over a 19‐month period, we identified 32 children (median age 8 months, range 3–14 months) who had undergone DV‐CTA and bronchoscopy within a 90‐day period of each other. All studies were unsedated and free‐breathing. The primary reasons for evaluation included noisy breathing, stridor, and screening for tracheomalacia. There was excellent agreement between DV‐CTA and bronchoscopy for diagnosis of tracheomalacia ( κ = 0.81, p < 0.001), which improved if children ( n = 25) had the studies within 30 days of each other ( κ = 0.91, p < 0.001). CTA provided incremental information on severity, and cause of secondary tracheomalacia. Conclusion: For most children, DV‐CTA requires no sedation or respiratory manipulation and correlates strongly with bronchoscopy for the diagnosis of tracheomalacia. Level of Evidence: 3 Laryngoscope, 133:410–416, 2023